Perspectives on barriers to traditional sources of sexual and reproductive health information and services: Are mHealth technologies the answer? - Alexander S Laar; Melissa L Harris; Clare Thomson; Deborah Loxton (Tabriz University of Medical Sciences, 2024)
Background: In Ghana, several qualitative studies have explored users' perspectives on conventional sources of sexual and reproductive health (SRH) information and factors which influence provision of and access in rural settings. However, there is a dearth of qualitative studies on healthcare provider (HCP) perspectives on factors that deter access to conventional sources of SRH information among young people in rural Ghana and innovative ways for addressing barriers. This study explored perspectives on barriers to traditional sources of SRH information and services and innovative ways of using mHealth technologies for addressing provision and access challenges among young people in rural Ghana. Methods: This study used a qualitative approach using in-depth interviews. Semi-structured in-depth interviews were conducted with HCPs in rural areas in three regions of Ghana between May and August 2021. Participants were selected from rural communities using the convenience snowball sampling and were interviewed via Zoom. The interviews explored the experiences and perceptions of HCPs on conventional SRH information and services and young people's access to this information and services. The interviews were audio recorded and transcribed verbatim. Data were analysed thematically using NVivo software version 12, following the approach outlined by Braun and Clarke. Results: Twenty HCPs were interviewed for this study. The participants identified different sources of SRH information and services used by rural young people. Peers or friends, health facilities, health providers, and community settings were reported as the main services and sources of SRH information. Participants reported several barriers and challenges to the provision of and access to SRH information to young people, including socio-cultural norms, religious beliefs, unfriendly health facility environments, negative health providers' attitudes, lack of privacy and confidentiality resulting in unfriendly youth SRH services, distance, and financial challenges due to costs of transportation which limits rural young people's access to, and use of, SRH services. All the participants indicated that in addressing provision and access barriers, the use of mobile phones could be beneficial. Conclusion: This study highlights several barriers and challenges that deter provision of, and access to, SRH information and services for young people in rural Ghana. The findings indicate the use of innovative mobile health (mHealth) technologies may be one solution to some of the barriers and challenges.